INTRODUCTION OF ‘SMALL GROUP TEACHING’ METHOD TO 1ST YEAR B.A.M.S. STUDENTS FOR IMPROVEMENT OF COGNITION - Visave Pratibha; Choudhari Deepali (International Journal of Applied Ayurved Research, 2019)
Introduction: There are several methods of teaching and learning (T-L method). Out of these didactic method is very common but it is one way communication. As students have passive role and different IQ levels, it is not so useful T-L method for better understanding of the subject. In such conditions there is a need of better T-L method for improvement of cognition of the students. So, ‘Small group teaching’ method is chosen for this educational research project. Methodology: It includes two phases viz. planning and execution. In Planning phase all the required documents and study material collected. 7 students from first year B.A.M.S were selected randomly to form small group and their consent taken before starting the project. In Execution phase, final project was implemented. Pre-test was carried out to check the existing knowledge of the student about the topic. Then, one by one total 5 handouts were given to them along with study material followed by discussion on ‘Anatomy of the stomach’ in all aspect. Then activity sheet was provided related to each handout. At the end post-test was given along with questionnaire in the form of Likert scale. Data collected and analyzed statistically by applying paired t-test. Result: The test result found statistically highly significant which indicates that the small group teaching method is very useful in improvement of cognition of students. Discussion: Small group teaching is very effective in improvement of cognition of students. This T-L method should be practiced in every educational institute so as to get deeper understanding of the subject. With the help of this, students can achieve quality learning outcomes. It will definitely be helpful for improving the learning environment too.